INNOVATIVE SOLUTIONS OF CIRCULAR ECONOMY WITHIN SUSTAINABLE ECONOMIC GROWTH AND THEIR INTEGRATION INTO INDUSTRIAL SECTORS (International Conference on Scientific Research in Natural and Social Sciences, 2025)
In recent years, Uzbekistan has been actively progressing towards a green economy, recognizing its crucial role in ensuring sustainable economic growth and environmental protection. The increasing urgency of addressing environmental challenges, such as air pollution, resource depletion, and inefficient waste management, underscores the need for innovative solutions. To accelerate this transition, the government has introduced strategic regulatory measures, including Decree of the presidential DP-4477 (dated October 4, 2019), which outlines the “Green Economy Transition Strategy for 2019–2030.”[1] This policy framework aims to optimize resource utilization, promote eco-friendly technologies, and enhance energy efficiency across various economic sectors. In alignment with this strategy, researchers and young scholars are actively engaged in scientific exploration to develop and implement sustainable economic models.